Simple ligation versus stump inversion in open appendicectomy: a systematic review and meta-analysis - Cubas, Vanessa; Karim, Ahmed; Waterland, Peter (International Surgery Journal, 2018)
To perform a systematic review and meta-analysis on post-operative complications after surgery for appendicitis comparing simple ligation with inversion of the appendix stump. PubMed, Medline and Embase databases were searched to identify studies comparing post-operative outcomes in appendicectomy following simple ligation and inversion of the appendix stump. A meta-analysis with a random-effects model was used to calculate pooled odds ratios (OR) and confidence intervals (CI) for each outcome measure of interest. A total of 14 studies were included for meta-analysis, comprising a total of 4037 patients who underwent appendicectomy. There was an increased risk of small bowel obstruction following appendix stump inversion (OR = 4.18, CI = 1.31 – 13.41; p = 0.02; 9 studies). After excluding studies without antibiotic prophylaxis there was no difference between inversion or ligation of the appendix stump with respect to either total infective complications (OR = 1.03; 95% CI= 0.75 – 1.43, 10 studies) or surgical site infection (OR = 1.07; CI = 0.78 – 1.47; 10 studies). Inversion of the appendix stump during appendicectomy may increase risk post-operative small bowel obstruction whilst offering no reduction in post-operative infective complications.